Misfortunes never come singly - Otrachshenko, Vladimir (2022)
Funding details: Robert Schalkenbach Foundation (funding number: 15-18-10014), Illinois Ornithology Society, FCT - Fundação para a Ciência e a Tecnologia (SFRH/BPD/122946/2016) and Fuel Cell Technologies Program. Funding text: Olga Popova acknowledges the support from the Russian Science Foundation (RSF) Grant No. 15-18-10014 "Projection of optimal socio-economic systems in turbulence of external and internal environment". Vladimir Otrachshenko acknowledges the research fellowship from Fundação para a Ciência e a Tecnologia, Portugal (SFRH/BPD/122946/2016). Vladimir Otrachshenko acknowledges the hospitality of the Leibniz Institute for East and Southeast European Studies (IOS), Regensburg, Germany, where the part of this paper was developed.